2022
DOI: 10.21118/apgs.v14i3.13039
|View full text |Cite
|
Sign up to set email alerts
|

Determinantes da Intenção de Rotatividade no Setor Público: um estudo em uma instituição federal de ensino

Abstract: Objetivo da pesquisa: Analisar os determinantes da intenção de rotatividade no setor público, verificando a influência das práticas de gestão de pessoas, da satisfação no trabalho e das características demográficas e ocupacionais na intenção de rotatividade dos servidores. Enquadramento teórico: O desligamento voluntário de profissionais pode gerar consequências negativas para a organização, tais como: custos para contratação e treinamento de novos trabalhadores; perda da identidade organizacional; e red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Other studies are also observed in the field of public HEIs that focus on questions related to turnover intention, job satisfaction, people management practices, and managerial innovation (Montenegro et al, 2021;Pinho et al, 2022b). When carrying out a recent study of employees in a public HEI, Pinho et al (2022b) highlighted that certain people management practices -involvement, job conditions, and remuneration and rewards -negatively influenced the employees' turnover intention. On the other hand, the aforementioned study identified that the recruitment and selection practice positively influences turnover intention.…”
Section: Public Higher Education Institutionsmentioning
confidence: 99%
“…Other studies are also observed in the field of public HEIs that focus on questions related to turnover intention, job satisfaction, people management practices, and managerial innovation (Montenegro et al, 2021;Pinho et al, 2022b). When carrying out a recent study of employees in a public HEI, Pinho et al (2022b) highlighted that certain people management practices -involvement, job conditions, and remuneration and rewards -negatively influenced the employees' turnover intention. On the other hand, the aforementioned study identified that the recruitment and selection practice positively influences turnover intention.…”
Section: Public Higher Education Institutionsmentioning
confidence: 99%